Desafíos de la pequeña y mediana empresa: un cluster de calzado en el Brasil - Swirski de Souza, Yeda (2002)
The purpose of this article is to develop a general analysis of how small businesses establish and conquer their market share in the Brazilian footwear cluster. The selected organizations, each of which gives rise to a case study, deserve special attention since they survive and improve their performance despite the limitations that the stratum of small businesses usually faces.